Longitudinal change of HBsAg in HBeAg-negative patients with genotype B or C infection. - Tung-Hung Su; Chun-Jen Liu; Tai-Chung Tseng; Chen-Hua Liu; Hung-Chih Yang; Chi-Ling Chen; Pei-Jer Chen; Jia-Horng Kao; Ding-Shinn Chen (PLoS ONE, 2013)
BACKGROUND & AIMS: Quantitative HBsAg has been recognized to assist in the management of chronic hepatitis B virus (HBV) infection. However, its role in disease monitoring of HBeAg-negative patients remains unclear. We aimed to investigate the longitudinal HBsAg change in HBeAg-negative carriers with HBV genotype B or C infection. METHODS: This is a retrospective cohort study conducted in a university hospital. Treatment-naïve HBeAg-negative carriers followed for more than 3 years were recruited. Their hepatitis activities were categorized by longitudinal HBV-DNA levels into high viral-load (HVL: HBV-DNA >/ =2000 IU/mL persistently), low viral-load (LVL: HBV-DNA <2000 IU/mL persistently) and fluctuated viral-load (FVL: HBV-DNA between HVL and LVL). The baseline and end-of-follow-up (EOF) HBsAg levels were quantified for analyses. RESULTS: We recruited 187 patients with a median follow-up of 8 years. LVL patients had a significantly lower HBsAg at baseline and EOF and a significantly greater annualized HBsAg decline compared with the FVL and HVL. The longitudinal HBsAg change was independent of genotype B or C. The lower baseline HBsAg level predicted the HBsAg decline and HBsAg loss, whereas the higher baseline HBV-DNA predicted the hepatitis flare. A baseline HBsAg <50 IU/mL predicted subsequent HBsAg loss with a sensitivity of 82% and specificity of 67%. The annualized HBsAg decline appeared non-linear, and accelerated as the HBsAg level lowered (0.054, 0.091, 0.126 log(10) IU/mL in patients with baseline HBsAg >1000, 100-999, <100 IU/mL, respectively, P for trend= .014). CONCLUSIONS: In genotype B or C HBeAg-negative carriers, baseline HBsAg levels correlate with future disease activities and help to predict HBsAg decline or loss. Inactive carriers with lower baseline HBsAg levels have a greater and accelerating HBsAg decline over time, regardless of HBV genotypes.